99mTc-pertechnetate cut-off to distinguish Graves\' disease from subacute thyroiditis - Amir Gholami; Mahsa Sabbaghi; Hoda Shirafkan; Seyyed Hossein Mousavie Anijdan (Caspian Journal of Internal Medicine)
Background: The cause of thyrotoxicosis can be determined through the thyroid uptake of 99mTc-pertechnetate. The goal of the study was to calculate the cut-off value of 99mTc-pertechnetate of the thyroid gland for the differential diagnosis of Graves' disease from subacute thyroiditis. Methods: A total of 60 patients were included in the study. Based on thyroid scan findings, 30 patients were in the Graves group and 30 of them had been diagnosed as subacute thyroiditis. Biochemical parameters, thyroid scintigraphy, and the percentage thyroidal 99mTc-pertechnetate uptake results were thoroughly assessed. Results: The mean percentage 99mTc-pertechnetate uptake in Graves group was much higher than that of the subacute thyroiditis group, which was statistically significant (P <0.001). Receiver operating characteristic (ROC) analysis revealed that the uptake cut-off value of 1.1% had the sensitivity and specificity of 97% and 95%, respectively. Conclusion: The findings depicted that the cutoff value of 1.1% for 99mTc-pertechnetate uptake could be a helpful index to differentiate Graves' disease from subacute thyroiditis, especially when it is difficult to distinguish between the two diseases using conventional diagnostic methods.